2011
DOI: 10.1007/s11999-011-1868-0
|View full text |Cite
|
Sign up to set email alerts
|

Precontoured Plating of Clavicle Fractures: Decreased Hardware-related Complications?

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 31 publications
5
84
2
4
Order By: Relevance
“…The radiological and clinical indications to perform osteosynthesis of mid-shaft clavicle fractures are still debated, and the suggested technique, choice of plate and position also vary in the literature [5,7,8,[10][11][12][13][14]. Despite the widespread use of locking plate osteosynthesis in clavicle fracture treatment, there is little clinical information about outcome and potential benefits of its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiological and clinical indications to perform osteosynthesis of mid-shaft clavicle fractures are still debated, and the suggested technique, choice of plate and position also vary in the literature [5,7,8,[10][11][12][13][14]. Despite the widespread use of locking plate osteosynthesis in clavicle fracture treatment, there is little clinical information about outcome and potential benefits of its use.…”
Section: Discussionmentioning
confidence: 99%
“…The precontoured locking plate is now the preferred choice of implant for surgical treatment of clavicle fractures [1,5,6]. The locking plate theoretically offers increased stability of fixation, which again should allow for application of greater forces than conventional reconstruction or dynamic compression plates (DCP) plates.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the S-shaped curve structure previously applied to the plate to conform to the curves of the clavicle, no bending or curving of the plate was made intraoperatively. In fact, previous studies reported that intraoperative bending and curving procedures applied to the plate for compatibility with the bone increased the fragility of the plate [11][12][13][14][15][16][17]. In the current study, no screw pull-out, screw breakage, plate breakage, or complications related to plate instability were observed in any patient.…”
Section: Discussionmentioning
confidence: 44%
“…Surgical treatment by plate fixation has fewer nonunions and better functional outcome compared to conservative treatment, as per Robinson CM [14] . Hardware prominence is one of the known complication which can be reduced by precontouring of the plate 15 . In our study, it was observed that rate of complication was higher in surgically treated patients with minor complications which is comparable to the study done by Judd et al [16] .…”
Section: Discussionmentioning
confidence: 99%